2014
DOI: 10.1037/a0037212
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of cognitive behavioral therapy and acceptance and commitment therapy for social phobia: Outcomes and moderators.

Abstract: Objective Cognitive behavioral therapy (CBT) is an empirically supported treatment for social phobia. However, not all individuals respond to treatment and many who show improvement do not maintain their gains over the long-term. Thus, alternative treatments are needed. Method The current study (N=87) was a 3-arm randomized clinical trial comparing CBT, Acceptance and Commitment therapy (ACT), and a waitlist control group (WL) in participants with a DSM-IV diagnosis of social phobia. Participants completed 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
157
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(172 citation statements)
references
References 57 publications
12
157
1
2
Order By: Relevance
“…Blanco et al [17] reported a lower response rate of CBT to social anxiety disorder compared to drug therapy and both treatments together. More over despite experiencing considerable Success [18] in a recent research [3], it has been reported that CBT had important shortcomings, such as not all individuals responded to this treatment, the long-term treatment outcomes were not stable, and, trying to control thoughts that accompany the unpleasant excitement, often increases them. Barlow et al [19] also reported that many recipients of CBT abandoned the treatment before it ends, and relapse following successful treatment, seeking additional treatment usually happened.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blanco et al [17] reported a lower response rate of CBT to social anxiety disorder compared to drug therapy and both treatments together. More over despite experiencing considerable Success [18] in a recent research [3], it has been reported that CBT had important shortcomings, such as not all individuals responded to this treatment, the long-term treatment outcomes were not stable, and, trying to control thoughts that accompany the unpleasant excitement, often increases them. Barlow et al [19] also reported that many recipients of CBT abandoned the treatment before it ends, and relapse following successful treatment, seeking additional treatment usually happened.…”
Section: Introductionmentioning
confidence: 99%
“…Barlow et al [19] also reported that many recipients of CBT abandoned the treatment before it ends, and relapse following successful treatment, seeking additional treatment usually happened. Crask et al [3] acknowledged that despite the successful treatment of people with anxiety disorders, they remain vulnerable to developing anxiety and mood disorders across the lifespan. Furthermore, there is growing interest in behavioral approaches that do not rely on cognitive restructuring, which is a substantial component of CBT, such as behavioral activation treatment for depression [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACT comprises six central processes which lead to psychological flexibility. These six processes include: 1) acceptance, 2) fusion, 3) self as a context, 4) relationship with the present, 5) values and 6) commitment (14). Acceptance and commitment are important substitutes which help to reach avoidance based on experiences.…”
Section: Introductionmentioning
confidence: 99%
“…ACT as a therapy which is based on acceptance and commitment, is a third-wave treatment behavior which clearly accepts changes in the mechanism of thoughts and feelings, instead of changing their shapes, contents, and frequencies (14). ACT is rooted in a philosophical theory called "functional contextualism", and it is based on a research plan connected to language and cognition, which is called "Intellectual Relationships Framework Theory".…”
Section: Introductionmentioning
confidence: 99%